Guarantees of human and citizen rights and freedoms in Ukraine and foreign countries - Rіabovol, Liliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
It is substantiated that at the current stage of the formation of Ukraine as an independent, democratic, legal, social state, the issue of guaranteeing the rights and freedoms of a person and a citizen has become particularly relevant. In the context of European integration, relevant experience in guaranteeing human rights accumulated in developed, primarily European, states is important for Ukraine. The purpose of the article is to summarize scientific positions on the definition of the concept of «guarantees of human and citizen rights and freedoms» and to systematize the types of guarantees by classification. It has been established that an effective system of domestic guarantees of the rights and freedoms of a person and a citizen is enshrined in Ukraine and in foreign countries at the legislative, primarily constitutional, level. It covers the following types of guarantees: general and special; legal, economic, political and organizational; material, procedural and organizational-legal (institutional) (it was found that the ombudsman institute plays a special role among them); judicial and extrajudicial. A special place among these guarantees is that the order, grounds and limits of the restriction of human rights and freedoms are established. It is proved that the classification of guarantees based on domestic constitutional and legal science is consistent with the classification developed in European law. It has been established that special attention in national and European law is focused on judicial protection as a human right and at the same time a guarantee of other human rights. It was established that domestic guarantees are complemented by international legal guarantees of human rights and freedoms. Among them, it is possible to single out international acts that directly enshrine human rights, as well as international bodies, organizations and institutions designed to ensure and contribute to the protection of these rights. It has been confirmed that the content of human rights guarantees provided for by Ukrainian legislation is based on international and European human rights standards. The definition of guarantees of human rights in democratic states is formulated as a whole set of legal and institutional means of domestic and international legal nature, judicial and extrajudicial, actually constitutional guarantees.